Capture réglementaire en temps de pandémie - Samira Guennif (Revue de la Régulation)
In the midst of the covid-19 pandemic, the Food and Drug Administration (FDA) published in March the orphan drug status granted to remdesivir, a molecule patented by Gilead as a treatment for the new coronavirus. This gave the company seven years of market exclusivity for its drug in the US market. This decision was immediately denounced as a clear misuse of the Orphan Drug Act (ODA) administered by the FDA under the influence of the pharmaceutical industry; a case of regulatory capture. The purpose of this article is to explore the concept of regulatory capture, drawing on work developed in the field of political science and (international) political economy, and based on the case study of remdesivir. It is shown that there have been multiple captures around a public good: agency, statutory, corrosive or cultural captures, to draw on the work of Carpenter (2014) developed in a break with those of economic regulation theory. Finally, recommendations are made to strengthen the ODA and limit its vulnerability to capture.